Cara-Cara Pembuatan Garam Di Indonesia - Kusartuti Imam Subagyo (Balai Besar Kimia dan Kemasan, 1977)
There are many proceses for making salt in indonesia. But all of these have an equality, they use sun energy for evaporation (solar salt), and generally based on sea water. Only 2 small areas in Central of Java, use soil water and salted mud for raw material (soil salt). The mentioned processes will be described briefly.